Mechanisms of Social Capital in Organizations: How Team Cognition Influences Employee Commitment and Engagement. Issue 7 (October 2019) - Kroll, Alexander; DeHart-Davis, Leisha; Vogel, Dominik
While previous research has shown that organizational social capital benefits organizations and creates performance gains, most of this work examined this relationship at the macro level based on organizational aggregates. In this article, we study organizational social capital effects at the micro level, that is, its impact on important work-related attitudes of employees within organizations. We argue that individual perceptions of organization-wide social capital matter in determining employee attitudes such as engagement and commitment. We also point to the critical role of team cognition in shaping individual perceptions of social capital in organizations. Using an organizationally representative sample of nearly 1, 200 individuals from two local government organizations in North Carolina, we find support for the indirect effect of team cognition on employee work attitudes. The findings suggest that a promising way to increase the social capital of organizations is through interventions at the team level.